Transaction cost of micro and small enterprises financing - Ghana Atma Sulistya; Darwanto Darwanto (Economic Journal of Emerging Markets)
High transaction costs become one of the obstacles for the micro and small enterprises (MSEs) to access financial loans to the bank. In order to minimize the transaction costs, group lending scheme become  alternative, so that both sides are pay lower transaction costs, and MSEs are able to improve their welfare. This study aims to analyze the credit process and transaction costs incurred on the model of individuals and groups lending and to compare the magnitude of transaction costs on both models. Mixed Method Analysis is used to analyze the component of transaction costs and the magnitude of the transaction cost on both models.These results indicate there are differences in transaction costs incurred on both schemes. In the amount of the transaction costs, the overall group scheme still allows for greater compared to individual schemes and dominated by the cost of the disbursement. Even so, the transaction cost per member group is much smaller than the individual schemes.